A retrospective review of nine cases of atypical neurosyphilis - Ran Miao; Canglin Song; Wenjing Zhang; Xiaoyang Ma; Yi Zhang; Yuming Huang (Frontiers in Medicine)
BackgroundNeurosyphilis may manifest in a form resembling autoimmune encephalitis, primarily characterized by cognitive impairment, psychiatric disorders, and seizures. Brain magnetic resonance imaging typically reveals unilateral or bilateral lesions in the mesiotemporal lobe and may also identify abnormalities in the inferior frontal lobe, parietal lobe, occipital lobe, and thalamus. Nevertheless, there are very few reports addressing this particular aspect.MethodsWe conducted a retrospective review of the medical records of inpatients diagnosed with neurosyphilis who presented with cognitive impairment, psychiatric disorders, and seizures. All patients underwent lumbar puncture and cerebrospinal fluid (CSF) examination. A total of nine inpatients were consecutively enrolled from Beijing Ditan Hospital between July 2019 and December 2024.ResultsSeven patients were male, while two patients were female. All patients presented with acute or subacute onset and had no fever prior to the onset. Four patients presented with seizures, two exhibited psychiatric and behavioral abnormalities, and three experienced memory decline. Throughout the course of the disease, a total of seven patients presented seizures. In the physical examination, all patients exhibited cognitive impairment. Regarding the CSF analysis, the initial results for one patient were inconclusive. The remaining patients demonstrated lymphocyte-predominant pleocytosis along with elevated CSF protein concentrations. One patient tested positive for the anti-CV2/CRMP5 antibody in both serum and CSF. Magnetic resonance imaging of the brain revealed that eight patients had sustained damage to the mesiotemporal lobe, while one patient demonstrated damage exclusively to the bilateral frontal and occipital lobes. Five patients exhibited sharp waves or sharp-slow waves on their electroencephalograms. All patients showed improvement in symptoms after antisyphilitic treatment for neurosyphilis.ConclusionNeurosyphilis may manifest with symptoms associated with the limbic system, and brain magnetic resonance imaging often reveals unilateral or bilateral lesions in the mesiotemporal lobe that resemble those seen in autoimmune encephalitis. Early intervention with antisyphilitic treatment has proven to be effective. Clinicians should remain vigilant for such atypical presentations of neurosyphilis.